Evaluation of The Effectiveness of Control Systems in Computerized Accounting Information Systems: An Empirical Research Applied on Jordanian Banking Sector - Hayale, Talal H.; Abu Khadra, Husam A. (JABM, 2006)
The objective of this study is to evaluate the level of Control Systems effectiveness in Computerized Accounting Information Systems (CAIS) that is implemented in the Jordanian banking sector to preserve confidentiality, integrity and availability of the banks data and their CAIS. An empirical survey using self-administrated questionnaire has been carried out to achieve the above-mentioned objectives. The study results reveal that Jordanian domestic banks are using effective fraud and error reduction controls. The study also reveals that these banks lack in the application of other Control System dimensions (Physical access, Logical access, Data security, Documentation standard, Disaster Recovery, Internet, communication and E-Control and Output security controls). The studys main recommendation is for Jordanian domestic banks to increase the CAIS control system strength for all dimensions, in order to avoid any possible threats that could threaten their CAIS.